Educator Excellence in the Era of Society 5.0: A Hadith Perspective - Onilivia, Viva Fadma; Noptario, Noptario (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: In the disruptive era of Society 5.0, educators are required to continuously learn and adapt to technological advancements. This study aims to examine the concept of an exemplary educator from the perspective of Hadith, providing a reference for teachers to develop their potential in accordance with religious teachings. Utilizing a qualitative research approach and library research methods, this study explores various sources such as books, articles, and other relevant literature. The findings emphasize that to be a quality educator in the sophisticated era of Society 5.0, one must be adept at embracing change, utilizing technology effectively, and guiding students towards both worldly success and spiritual fulfillment. The discussion underscores the importance of balancing technological proficiency with religious principles, portraying educators as critical thinkers who embody the teachings of Prophet Muhammad SAW. This study contributes to the Islamic educational knowledge base by highlighting that the efforts to create excellent educators are also advocated in Islam through Hadith, thereby ensuring that future generations receive the best education aligned with religious teachings. Abstrak: Di era disruptif Society 5.0, pendidik dituntut untuk terus belajar dan beradaptasi dengan kemajuan teknologi. Penelitian ini bertujuan untuk mengkaji konsep pendidik yang unggul dari perspektif hadis, memberikan referensi bagi guru untuk mengembangkan potensinya sesuai dengan ajaran agama. Menggunakan pendekatan penelitian kualitatif dan metode penelitian kepustakaan, studi ini mengeksplorasi berbagai sumber seperti buku, artikel, dan literatur relevan lainnya. Temuan menekankan bahwa untuk menjadi pendidik yang berkualitas di era Society 5.0 yang canggih, seseorang harus mampu menghadapi perubahan, memanfaatkan teknologi secara efektif, dan membimbing peserta didik menuju kesuksesan duniawi dan pemenuhan spiritual. Pembahasan ini menekankan pentingnya keseimbangan antara kecakapan teknologi dan prinsip-prinsip agama, menggambarkan pendidik sebagai pemikir kritis yang meneladani ajaran Nabi Muhammad SAW. Penelitian ini berkontribusi pada khazanah pengetahuan pendidikan Islam dengan menyoroti bahwa upaya menciptakan pendidik yang unggul juga dianjurkan dalam Islam melalui hadis, sehingga generasi masa depan dapat menerima pendidikan terbaik yang sesuai dengan ajaran agama.